Television Goes Mobile: the Transformation of the Audio-Visual Media Market - Martišius, Mantas (Information & Media, 2018)
[full article, abstract in English; abstract in Lithuanian]The 21st century is often called the age of information, and the society of this age is often dubbed the society of information and news. Meanwhile, a rapid and efficient transmission of news and the prioritization of this process have become relevant at least already back in the 90s. Information volumes consumed by the society have been growing by the day. Progress in technologies and communication have eliminated time and space barriers. The aim of this article is to answer how and when linear television is going to move online and especially to mobile networks. This aim is broken down into the objective of analyzing issues pertaining to the definition of television, the overview of the impact of media convergence on television, the analysis of the issues related to the definition of television and internet television, and the analysis of prospects for linear versus internet television. The article may be relevant for media experts and analysts, media regulators, users, and the creators of internet television content.
Keywords: television; video on demand; mobile internet; system of audiovisual market; convergence and transformation